PROBLEMS AND PROSPECTS OF SUSTAINABLE DEVELOPMENT OF AGRICULTURE - D.A. Tleuzhanova; D.S. Kurmanova; A.A. Beisembaeva; M.N. Nurgabylov (Academic Journal of Physical and Chemical Sciences, 2019)
Rural territories of Kazakhstan are the most important socio-economic and ecological subsystem of society. They have specific features, their own goals, objectives, principles, criteria and development indicators. Here are concentrated significant human, natural and industrial resources, industries, the effective development of which can significantly improve the state of the economy and raise the standard of living of the population of the state. The authors believe that the unfavorable demographic situation in the Republic of Kazakhstan, as a result of which the decline in the rural population is progressing. In accordance with this, in the context of the issue being studied, first of all it is advisable to consider the indicators characterizing the standard of living of the population in rural areas of the Akmola region of Kazakhstan. Currently, the development of rural areas of Kazakhstan attracts the attention of a wide range of specialists who are trying to build the conceptual foundations of this process.